RETRACTED: Globalization and local service businesses: A study of small business contributions to service industry development - Nasimov Dilmurod; Yekimov Sergey; Arabov Nurali; Bozorov Berdimurod; Ulugmuradova Nodira; Tukhliev Bakhtiyor (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001